95. Impact of Penetrating Trauma on Surgical Site Infection Standardized Infection Ratio (SIR) for Colon Procedures. (4th December 2021) - Boston, Kelley M; Ellsworth, Misti; Thomas, Jocelyn; McInnis-Cole, Tawanna A; Ostrosky-Zeichner, Luis
Abstract: Background: Colon surgery (COLO) is one of the focus areas for the the Centers for Medicare and Medicaid Services (CMS) Hospital Inpatient Quality Reporting (IQR) Program. Standardized criteria from the National Healthcare Surveillance Network (NSHN) are used to define surgical site infections (SSI) and to assess and weight standardized risk variables, so that all organizations can be judged to the same standard. Performance is compared though use of a standardized infection ratio (SIR), which is the observed number of infections, divided by the "predicted" number of infections, given the number and type of surgeries performed. Methods: A retrospective review of medical records and NHSN documentation was conducted for 778 COLO procedures that were performed at a large academic and level 1 trauma center between January 2019 and December 2020. Initial review of the data showed that the increases in SIR were primarily concentrated in trauma patients with intestinal injury and fecal spillage. SIR for adult procedures were calculated using the NHSN Complex 30-Day SSI Data for IQR Report model, which the metric used by the CMS IQR. The CDC NHSN Statistics Calculator was used to compare SIR for procedures coded as trauma and non-trauma. As a proxy for patients with penetrating trauma, SIR for patients coded as trauma who had a surgical wound class noted as dirty was compared to SIR for patients coded as trauma with surgical wound class coded as contaminated or clean-contaminated. Results: For the CMS model, there was a statistically significant difference (p = 0.0003) between SIR for trauma (SIR = 3.451) and non-trauma (SIR = 1.071) procedures. There was also a statistically significant difference (p=0.0014) between trauma procedures with dirty surgical wound class (SIR = 6.608), compared to those with wounds categorized as contaminated or clean-contaminated (SIR = 2.235). NHSN Adult Complex 30 Days SIR comparison for COLO SSI with and without trauma NHSN Adult Complex 30 Days SIR comparison for trauma COLO procedures with dirty wound class description, against COLO procedures with wound class described as clean or clean-contaminated Conclusion: Risk factors currently included in the model for COLO SSI may not adequately account for the increased risk from penetrating trauma with fecal spillage. Trauma and wound class should be added to the CMS IQR risk model for SIR. Disclosures: Kelley M. Boston, MPH, CIC, CPHQ, FAPIC, Infection Prevention & Management Associates (Employee, Shareholder) Luis Ostrosky-Zeichner, MD, Amplyx (Consultant)Cidara (Consultant)F2G (Consultant)Gilead (Grant/Research Support, Speaker's Bureau)Pfizer (Scientific Research Study Investigator, Speaker's Bureau)Scynexis (Grant/Research Support, Scientific Research Study Investigator)Viracor (Consultant)